Industrial Assessment of the Carbonate Rocks of the Pila Spi Formation at Haibat Sultan Mountain, Iraqi Kurdistan Region - Sissakian, Varoujan K.; Hamawandy, Mohammed J.; Ibrahim, Rahel K. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
The Pila Spi Formation is one of the prominent formations forming continuous ridges in Kurdistan Region. The thickness of the formation ranges from 15 to 110 m, consisting of well-bedded limestone, dolomite, dolomitic limestone, and very rare marl beds. The study area is located about 15 km east of Koya town, next to the abandoned tunnel through a deeply cut valley which has exposed 50 m of the formation. However, the uppermost part of the exposed section may belong to one of the Oligocene formations of Kirkuk Group. The study area was selected within the Pila Spi Formation because the rocks of the same formation and along the same ridge, about 45 km west of the study area showed encouraging results for cement industry. The average CaO is about 51%, whereas the average MgO is 1.8%. Therefore, eight samples were collected at constant thickness from the exposed section. The samples were subjected to X-ray fluorescence (XRF) test to indicate the main oxides in the sampled section. The acquired results from the XRF tests showed that the chemical composition of the exposed rocks within the Pila Spi Formation is suitable for cement industry, also for paper and paint but needs some treatment. Accordingly, another eight samples were collected from the same section to increase the density of sampling, totaling to 16 samples.